3x-6=8x+19

Simple and best practice solution for 3x-6=8x+19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6=8x+19 equation:


Simplifying
3x + -6 = 8x + 19

Reorder the terms:
-6 + 3x = 8x + 19

Reorder the terms:
-6 + 3x = 19 + 8x

Solving
-6 + 3x = 19 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-6 + 3x + -8x = 19 + 8x + -8x

Combine like terms: 3x + -8x = -5x
-6 + -5x = 19 + 8x + -8x

Combine like terms: 8x + -8x = 0
-6 + -5x = 19 + 0
-6 + -5x = 19

Add '6' to each side of the equation.
-6 + 6 + -5x = 19 + 6

Combine like terms: -6 + 6 = 0
0 + -5x = 19 + 6
-5x = 19 + 6

Combine like terms: 19 + 6 = 25
-5x = 25

Divide each side by '-5'.
x = -5

Simplifying
x = -5

See similar equations:

| 15x-2x=9 | | P=i(24)-i^2(1.5) | | 4.5s-3.5t=19 | | w+0.16w=6.38 | | 9.8=x+8.9 | | 6.666x-7=0.25x-2 | | 13+15+18+1= | | 873-8= | | (7a+5t)(7a-5t)= | | 5x-1=7x+2 | | 7+2a-3=-9 | | 215=90+(10+8) | | 10x+9=11x | | 6.66666666666666666666666666666666666666666666666x-7=0.25x-2 | | 2-x=x+1 | | e=290+.07(1310) | | a+5.8=34.8 | | =90+(10+8) | | 18=8+2m | | (x-1)x(x+1)=1320 | | 60.00+42.95=57.95 | | 0.20x+0.05(6-x)=0.10(30) | | a(5)+b(-9)=c | | 7x-8=-8+5 | | 3x+17=-10 | | -2(x-5)+10=10 | | -(-3a+1)=3a-1 | | 3(x+-2)=x+7 | | p^2+9p= | | 5x^2-10x+20=4x^2-2x+5 | | 3x+7=12x-4 | | 90+(10+8)= |

Equations solver categories